(untitled) (Brazilian Journal of Radiation Sciences, 2021)
Monte Carlo simulations are performed for a vertical S-shaped neutron guide for the cold neutron sources of the FRM-II, HZB and PSI reactors through the McStas software. The aim of our study is investigate a relation between the cutoff in the cold neutron spectrum and the sources. Results for the neutron flux at the sample position are presented for different supermirrors with m = 1, 2 and 3. The vertical S-shaped neutron guides additionally provide a vertical displacement between beam hole and sample position, which can facilitate the implementation and manipulation of sample environments.